Intravenous lidocaine in the management of chronic peripheral neuropathic pain: a randomized-controlled trial - Moulin, Dwight E.; Morley-Forster, Patricia K.; Pirani, Zameer; Rohfritsch, Cathy; Stitt, Larry (Canadian journal of anesthesia, 2019)
Purpose Neuropathic pain, resulting from injury to the peripheral or central nervous system, is due to upregulation of aberrant sodium channels with neuronal hyperexcitability. Lidocaine blocks these channels and several studies show that intravenous (IV) lidocaine infusion provides significant relief in patients with chronic peripheral neuropathic pain in the short term (for up to six hours). Our objective was to determine if IV lidocaine provides significant pain relief and overall improvement in quality of life in the longer term (for up to four weeks). Methods This single site randomized double-blind, crossover trial compared IV lidocaine infusion (5 mg·kg −1 ) with active placebo infusion containing diphenhydramine (50 mg) in patients with chronic neuropathic pain of peripheral nerve origin of at least six months duration. The primary outcome was average pain intensity reduction from IV lidocaine relative to placebo at four weeks post-infusion. Secondary outcome measures included parameters of physical function, mood, and overall quality of life. Results We enrolled 34 subjects in this trial—mostly with painful diabetic neuropathy and post-herpetic neuralgia. There were no significant differences between IV lidocaine and placebo infusions at any time point involving any of the outcome measures. Mean (standard deviation) pain intensity at week 4 for the placebo and lidocaine groups were not different [6.58 (1.97) vs 6.78 (1.56), respectively; between-group difference, 0.17; 95% confidence interval, − 0.50 to 0.84]. Conclusion We found no significant long-term analgesic or quality of life benefit from IV lidocaine relative to control infusion for chronic peripheral neuropathic pain. Trial registration clinicaltrials.gov (NCT01669967); registered 22 June, 2012.